Kajian Etnofarmasi Tumbuhan Obat di Kawasan Geotermal Ie Seum, Aceh Besar: Eksplorasi Pengetahuan Tradisional dan Potensi Farmakologis. - Fakri, Fajar; Isnaini , Nadia; Nasution , Muhammad Amin; Bakri , Tedy Kurniawan; Illian , Didi Nurhadi; Muhni , Akmal; Andry , Muhammad (Journal of Pharmaceutical and Sciences, 2025)
Indonesia is recognised as one of the world's megadiverse countries, possessing extraordinary biological wealth, including the medicinal plant potential in the geothermal area of Ie Seum, Ie Seum Village, Mesjid Raya Subdistrict, Aceh Besar District. This study aimed to explore and document local communities' traditional knowledge regarding using medicinal plants through an ethnopharmaceutical approach. A descriptive qualitative method was employed, with data collected via semi-structured interviews and participatory observation involving purposively selected informants. The findings identified nine medicinal plant species, with Eupatorium inulifolium and Vitex pinnata demonstrating the highest use value (UV) scores of 0.750 and 0.438, respectively, indicating their dominant usage in traditional healing practices. Leaves were the most frequently utilised plant parts, with standard preparation methods including boiling and pounding. These plants have traditionally been used to treat various health conditions, including fever, wounds, skin infections, and digestive disorders. The findings highlight the richness of traditional knowledge in Ie Seum and its potential as a foundation for developing natural product-based medicines. The extreme environmental conditions of the geothermal area are believed to influence the bioactive metabolite composition of the plants, potentially enhancing their pharmacological properties. This study underscores the importance of preserving local knowledge and encourages further scientific exploration to support the sustainable use of medicinal plants in developing traditional medicines.